Pathogenicity, mating type distribution and avirulence gene mutation of Magnaporthe oryzae populations in the Wuling Mountain region of China. (December 2021) - Xu, Xin; Tang, Xianying; Han, Haojie; Yang, Wu; Liu, Xinqiong; Li, Kai; Tan, Yanping; Qin, Yonghua; Liu, Xuequn; Wang, Chuntai
Abstract: Due to its unique natural conditions, the Wuling Mountain region is a key area of prevention and control of rice blast disease in China and an ideal area for investigation of its causal fungus, Magnaporthe oryzae ( M. oryzae ) research. A total of 237 M. oryzae isolates collected from the Wuling Mountain region in 2017–2018 were used for the study of genetic diversity and pathogenicity dynamics. A set of differential varieties (DVs), including 7 Chinese DVs, 12 Japanese DVs and 21 monogenic lines, were established, which differentiate the 237 isolates in this study into different physiological races. Cluster analysis of the combined molecular marker system (RAPD, REMAP, rep-PCR and the avirulence (Avr) gene) results showed that Baiyang and Jianshi had the greatest genetic diversity, which is consistent with the pathogenic results. The proportion of the two mating types was roughly equal each year; however, the dominance of the mating type between the two years was opposite. Furthermore, four isolates contained both mating types, which were assumed to be dual maters. Isolates with amplified bands of Avr gene s ( Avr-Pizt and Avr-Pita ) and corresponding pathogenicity were selected for Sanger sequencing. The result showed that point mutations and small indels resulted in the loss of avirulence function, indicating that mutations are potential mechanism for the rich pathogenic and genetic diversity of M. oryzae in the Wuling Mountain region. Highlights: 237 Magnaporthe oryzae field isolates collected from the Wuling Mountain region. Efficient Differential Varieties established to differentiate physiological races. First report of mating types of Magnaporthe oryzae populations in the region. Avirulenence genes mutations are potential mechanism for pathogenic and diversity.